2018
DOI: 10.3847/1538-3881/aae3eb
|View full text |Cite
|
Sign up to set email alerts
|

Plausible Home Stars of the Interstellar Object ‘Oumuamua Found in Gaia DR2

Abstract: The first detected interstellar object 'Oumuamua that passed within 0.25 au of the Sun on 2017 September 9 was presumably ejected from a stellar system. We use its newly determined non-Keplerian trajectory together with the reconstructed Galactic orbits of 7 million stars from Gaia DR2 to identify past close encounters. Such an "encounter" could reveal the home system from which 'Oumuamua was ejected. The closest encounter, at 0.60 pc (0.53-0.67 pc, 90% confidence interval), was with the M2.5 dwarf HIP 3757 at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…as widely used in previous studies (for example Bailer-Jones et al (2018) and Zuluaga et al (2018)). The length scales a and b are tuned to reflect the geometries of the galactic disk, bulge, and halo components.…”
Section: Our Model Of the Milky Way Galaxymentioning
confidence: 99%
See 1 more Smart Citation
“…as widely used in previous studies (for example Bailer-Jones et al (2018) and Zuluaga et al (2018)). The length scales a and b are tuned to reflect the geometries of the galactic disk, bulge, and halo components.…”
Section: Our Model Of the Milky Way Galaxymentioning
confidence: 99%
“…The initial conditions of 'Oumuamua at −3000 years are provided by Bailer-Jones et al (2018). Throughout our determination of possible source regions of 'Oumuamua in section 3.3, we characterize the uncertainty in their 2k=2 solution for 'Oumuamua's orbit by generating 100 clones of 'Oumuamua, each having an initial velocity randomly sampled from a distribution whose mean and standard deviations are recorded in Bailer-Jones et al (2018). We do the same with our own determination of the state of 'Oumuamua at -10 000 years in the past, but the initial positions as well as the velocities are randomly sampled.…”
Section: Initial Conditions Of 'Oumuamuamentioning
confidence: 99%
“…The third closest encounter from Hallatt & Wiegert (2019), at 0.32-0.55 pc (90% CI), is with 2MASS J03552337+1133437 (= Gaia DR2 3303349202364648320). Our solutions put this much further away, at 1.07 pc (90% CI 0.98-1.17 pc), so it is not listed in our table. tential and its evolution (e.g., Bailer-Jones et al 2018a;Zhang 2018;Hallatt & Wiegert 2019).…”
Section: Other Candidatesmentioning
confidence: 99%
“…Because of the lack of activity, it was surprising when the astrometry showed a strong non-gravitational signal that was perturbing the motion of 1I/'Oumuamua as it left the solar system, suggesting that there was undetected cometary outgassing (Micheli et al calj@mpia.de 2018). The non-Keplerian trajectory was compared with the reconstructed orbits of 7.4 million stars from the Gaia Data Release 2 (Gaia DR2) catalog to try to identify past close encounters that might be 1I/'Oumuamua's parent star system, but no low velocity close encounters were found (Bailer-Jones et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Work was done also in the field of extragalactic studies, for example on Quasars variability (Hwang et al, 2019) or gravitational lensing (Wertz et al, 2019). Gaia DR2 data have even been used to search for a plausible home star for the interstellar object 'Oumuamua (Bailer-Jones et al, 2018), which recently was discovered transiting in the solar system 12 . Summarizing such a huge and diverse body (2017) as entirely new, a simple ADS search showed that the cluster was already known in the past (Auner et al, 1980).…”
Section: The Second Gaia Data Releasementioning
confidence: 99%